Measuring the Creative Process: A Psychometric Examination of Creative Ideation and Grit. Issue 1 (2nd January 2018) - Rojas, Joanne P; Tyler, Kenneth M
Abstract : Within the investment theory of creativity (Sternberg & Lubart, 1996), creativity is defined as a 2-part process of buying low by investing in unusual ideas and then selling high by convincing others of the value or usefulness of these new ideas. This process requires both creative ideation and perseverance. The purpose of this research was to examine the psychometric properties of instrumentation proposed to assess the 2 underlying constructs in this definition: the creative ideational behavior required to buy low and the persevering behavior required to sell high. In particular, psychometric properties of a creativity ideation measure, the Runco Ideational Behavior Scale (RIBS Scale: Runco, Plucker, & Lim, 2001) and a perseverance measure, the Grit Scale (Duckworth, Peterson, Matthews, & Kelly, 2007) were examined in this study. Two samples of undergraduate students ( N  = 187; N  = 817) completed a survey including these two scales and demographic information. Factor analyses were performed on the RIBS and Grit Scales. The RIBS Scale was found to have a 2-factor structure and 2 proposed new subscales. The Grit Scale's previously reported 2-factor structure was confirmed.